Synthesis of Sodium Lauryl Sulfate (SLS) and Hexadecyltrimethylammonium Bromide (HDTMA-Br) Surfactant-Modified Activated Carbon as Adsorbent for Pb2+ and NO3- - Arnelli Arnelli; Rahmatul Fazira; Yayuk Astuti; Ahmad Suseno (Jurnal Kimia Sains dan Aplikasi, 2020)
The adsorption efficiency and selectivity of activated carbon as an adsorbent for ions can be improved. One way is to convert activated carbon into surfactant modified activated carbon (SMAC). The surfactants used in this study were the anionic surfactant Sodium Lauryl Sulfate (SLS) and the cationic surfactant hexadecyltrimethylammonium bromide (HDTMA-Br). This research aims to synthesize SMAC to obtain a material with a surface charge and absorb ions better than activated carbon. This research consisted of four stages. The first step was the carbonization of rice husks using a pyrolysis reactor at 400°C for 1 hour. The second stage was carbon activation using 30% ZnCl2 and microwave radiation for 5 minutes and 400 W. The third stage was the modification of activated carbon and characterization by FTIR, SEM, SAA. The fourth stage was the adsorption of Pb cations and nitrate anions by carbon, activated carbon, and SMAC. Several variables were applied, such as the type of surfactant, time, and method of modification. There are three ways of modification: (1) method A, in which activated carbon is brought into contact with SLS then HDTMA-Br. (2) Method B in which activated carbon was contacted with HDTMA-Br then SLS. (3) Method C in which activated carbon was brought into contact with SLS together with HDTMA-Br. All variables were investigated. The results showed that the optimum time for making SMAC for both surfactants was 4 hours, the optimum concentrations of SLS and HDTMA-Br were 60 and 300 ppm, respectively. SMAC made by the C method was the most effective at adsorbing Pb2+ and NO3- with adsorption capacities of 1.376 and 0.896 mg/g, respectively. The success of SMAC synthesis was evidenced by the S=O and (CH3)3N+ groups in the FTIR spectra. The SMAC surface area is smaller than activated carbon, 14.472 m2/g, but the surface morphology is smoother and more homogeneous.